Relações de gênero, poder e resistência na formação inicial de professores/as de educação física - Oliveira, Myllena Camargo de (2020)
Throughout history, men and women have had unequal opportunities for sports. Whereas men constitute the sports canon, women continue to fight to guarantee their right to practice any sport. Thus, we aim to explore the relationships between feminist waves and the participation of women in sport to understand the historical origins that mark the relations of gender, power and resistance that cross and constitute the collective sports disciplines in a Physical Education Degree course. The work was organized in two moments: first, we aimed to explore the relationship between the four feminist waves articulated to the insertion and the permanence of women in sports and, at the same time, to show how women break down sports barriers, engage in feminist movements and expand their adherence to sports, through a bibliographic research produced from national and international books and journals and inspired by the Foucauldian discourse analysis. The analyses show that in the first two feminist waves, women sought to win the right to vote and to their own body whereas in sports they fought against the ban on women in the field and the stereotypes arising from their insertion in sports. In the third wave, the struggle converged against essentialisms and in favor of the plurality of daily experiences and practices. Boosted by social networks, in the fourth wave, we fight against everyday violence and for equity in sports. In the second step, we aimed to understand the relations of gender, power and resistance that emerge among students and cross the disciplines of collective sports in a Physical Education degree course. In this ethnographic qualitative research, 86 students from 4 collective sports disciplines participated. The research sources were produced in the second half of 2019 in a university institution in the inland of the state of Rio Grande do Sul by participant observation, focus groups and interviews, submitted to data triangulation, with the aid of the software Nvivo 12, and to the Foucauldian discourse analysis. The results show that men and women reproduce the sports canon and reinvent relationships. Men often occupy privileged positions in games and women are positioned as supporting players. However, women and some men produce multiple resistances to access, remain and transform the sporting context. When approaching the results of the studies produced, we found that the incursion into feminist movements, exploring the relationships between women and sport, allowed us to identify that feminisms did not uneasy the collective sports classes in the initial training of physical education teachers since we still observe that certain men occupy privileged positions in the games. In contrast, women and some men, when producing resistance, rehearse new relationships and approach the powerful movement of the fourth feminist wave.